The role of nutritional fiber deficiency in the pathogenesis and course of gastroesophageal reflux disease - S. V. Morozov; Yu. A. Kucheryavyy; M. D. Kukushkina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the Review. To analyze current data about possible influence of nutritional fiber on the course of GERD.Key points. Systematic review in PubMed/Medline databases was performed with keywords food, dietary fiber in combination with gastroesophageal reflux, GERD. The review contains data concerning influence of nutritional fiber on the pathogenetic mechanisms of GERD and illuminates results of epidemiological studies suggesting positive correlation between quantities of nutritional fiber in the patient’s diet and manifestations of the disease. The main features of pathogenesis caused by the lack of nutritional fiber include slow gastric emptying, increased gastric volume, increased risk of obesity and hiatal hernia, reduced lower esophageal sphincter pressure. The epidemiological studies suggest the higher incidence of GERD symptoms, higher prevalence of Barrett’s esophagus and esophageal adenocarcinoma in patients who consume low quantity of nutritional fiber.Conclusion. Despite the lack of interventional studies the literature data about impact of nutritional fiber on the manifestations of GERD show probable approach for the correction of diet in GERD patients. There is a need for prospective studies evaluating correction of diet on the course of the disease.